In vivo transposon mutagenesis of the methanogenic archaeon Methanosarcina acetivorans C2A using a modified version of the insect mariner-family transposable element Himar1 - Zhang, J. K. (The National Academy of Sciences, 2000)
We present here a method for in vivo transposon mutagenesis of a methanogenic archaeon, Methanosarcina acetivorans C2A, which because of its independence from host-specific factors may have broad application among many microorganisms. Because there are no known Methanosarcina transposons we modified the mariner transposable element Himar1, originally found in the insect Hematobia irritans, to allow its use in this organism. This element was chosen because, like other mariner elements, its transposition is independent of host factors, requiring only its cognate transposase. Modified mini-Himar1 elements were constructed that carry selectable markers that are functional in Methanosarcina species and that express the Himar1 transposase from known Methanosarcina promoters. These mini-mariner elements transpose at high frequency in M. acetivorans to random sites in the genome. The presence of an Escherichia coli selectable marker and plasmid origin of replication within the mini-mariner elements allows facile cloning of these transposon insertions to identify the mutated gene. In preliminary experiments, we have isolated numerous mini-mariner-induced M. acetivorans mutants, including ones with insertions that confer resistance to toxic analogs and in genes that encode proteins involved in heat shock, nitrogen fixation, and cell-wall structures.